CIRCULAR AGRICULTURE - APPROACH AND DEVELOPMENT ORIENTATION FOR THE MEKONG DELTA - Ngo Van Thao, (HUIT Journal of Science, 2025)
Circular agriculture is a production model that applies the principles of circular economy to optimize resource use and minimize waste. In the context of agricultural production in the Mekong Delta, which has recently shifted towards monoculture, there are many pressures for sustainable development, such as ecological imbalance, disease outbreaks, and crop variety degradation. This report focuses on summarizing the theoretical foundations of the current circular economy and relating practical examples of agricultural production models being implemented in the Mekong Delta concerning the application of circular agriculture. Proposed approaches and orientations for the development of circular agriculture for the Mekong Delta include: (i) Optimizing the use of biomass; (ii) Effective resource management; and (iii) Reducing food waste to create a sustainable and reliable food system.